ANALISIS E-LEARNING READINESS (ELR) SEBAGAI INOVASI MEDIA PEMBELAJARAN BAHASA ARAB DI MAN 3 JOMBANG PADA MASA PANDEMI - Afif Kholisun Nashoih; Nia Safirotul Hidayah (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2021)
The Covid-19 pandemic has had a major impact on changing the learning system in Indonesia, from the face-to-face learning system to distance learning by utilizing e-learning. This research was conducted as an effort to analyze the level of e-learning readiness in learning Arabic at MAN 3 Jombang during the pandemic, in order to determine the effectiveness of the use of e-learning. This research is a descriptive research supported by primary data in the form of numbers, so the approach in this research is quantitative. Data was collected using two techniques, namely observation and distributing questionnaires. The results of the study revealed that the teachers in implementing e-learning in learning Arabic were considered ready. This is based on the achievement of the score on the aspect of personal ability of 79.7%, the aspect of material development and online delivery reaching a value of 80.9%, and the aspect of carrying out online evaluations obtaining a value of 75.6%, so that the three indicators are classified as in good qualification.